Assessment of clinical criteria for sepsis—was the cart put before the horse? - Aublanc, Mylène; Richard, Jean-Christophe (Journal of Thoracic Disease, 2016)
Sepsis is a worldwide major healthcare problem, with an estimated burden of 31.5 million cases treated each year around the globe, accounting for 5.3 million death per annum (1). Despite decades of intense research, there is to date no gold standard to define sepsis. Several international conferences have previously addressed this issue.